Renal Function Effect on the Association Between Body Mass Index and Mortality Risk After Acute Myocardial Infarction - Kang, Shin Yeong; Kim, Weon; Kim, Jin Sug; Jeong, Kyung Hwan; Jeong, Myung Ho; Hwang, Jin Yong; Hwang, Hyeon Seok (Frontiers in Cardiovascular Medicine, 2021)
Background: Body mass index (BMI) is a critical determinant of mortality after acute myocardial infarction (AMI), and higher BMI is associated with survival benefit in patients with renal impairment. However, there are no studies investigating the interactive effects of BMI and renal function on mortality risk after AMI occurrence. Methods: We enrolled 12,647 AMI patients from Korea Acute Myocardial Infarction Registry between November 2011 and December 2015. Patients were categorized based on estimated Glomerular Filtration Rate (eGFR) and BMI. The primary endpoint was all-cause mortality after AMI treatment. Results: Within each renal function category, the absolute mortality rate was decreased in patients with higher BMI. However, the adjusted hazard ratio (HR) of all-cause mortality for higher BMI was decreased as renal function worsened (adjusted HR [95% confidence interval] at BMI ≥25 kg/m2: 0.63 [0.41- 0.99], 0.76 [0.59-0.97], and 0.84 [0.65-1.08] for patients with eGFR ≥ 90, 90-45, and <45 mL/min/1.73m2, respectively). There was a significant interaction between BMI and renal function (P for interaction = 0.010). The protective effect of higher BMI was preserved against non-cardiac death and it was also decreased with lowering eGFR in competing risks models (adjusted HR at BMI ≥25 kg/m2: 0.38 [0.18- 0.83], 0.76 [0.59-0.97], and 0.84 [0.65-1.08] for patients with eGFR ≥ 90, 90-45, and <45 mL/min/1.73m2, respectively; P for interaction = 0.03). However, renal function did not significantly affect the association between BMI and risk of cardiac death (P for interaction = 0.20). Conclusions: The effect of BMI on the mortality risk after AMI was dependent on renal function. The association between greater BMI and survival benefit was weakened as renal function was decreased. In addition, the negative effect of renal function on the BMI – mortality association was pronounced in the non-cardiac death.